Rapid Turbidimetric Assay to Determine the Potency of Daptomycin in Lyophilized Powder - Eliane Gandolpho Tótoli; Hérida Regina Nunes Salgado (MDPI AG, 2015)
Daptomycin is an important antimicrobial for clinical practice, mainly because it remains very active against Gram-positive resistant strains, such as methicillin-resistant Staphylococcus aureus and vancomycin-resistant enterococci. Development of microbiological methods for the analysis of antimicrobials is highly recommended, since they can provide important information about their biological activities, which physicochemical methods are not able to provide. Considering that there are no studies in the literature describing microbiological methods for the analysis of daptomycin, the aim of this work was to validate a microbiological method for the quantitation of daptomycin by the turbidimetric assay. Staphylococcus aureus was used as the test microorganism, and the brain heart infusion broth was used as the culture medium. The validation of the method was performed according to the ICH guidelines, and it was shown to be linear, precise, robust, accurate and selective, over a concentration range of 8.0 to 18.0 µg mL−1. Student's t-test showed the interchangeability of the proposed method with a previously-validated HPLC method. The developed turbidimetric method described in this paper is a convenient alternative for the routine quality control of daptomycin in its pharmaceutical dosage form.